PENERAPAN MODEL COOPERATIVE LEARNING TIPE THINK PAIR SHARE UNTUK MENINGKATKAN PEMAHAMAN MATEMATIS PESERTA DIDIK KELAS V SEKOLAH DASAR NEGERI BINTARA VI - Putri, Aulia Natasya; Mira Amelia Amri; Arita Marini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to improve the mathematical understanding of 5th-grade students at SDN Bintara VI by implementing the Think Pair Share (TPS) cooperative learning model. The study was motivated by the low level of mathematical understanding in class V-A, where initial data showed that 73.3% of students failed to reach the minimum passing grade (KKM) of 75. The methodology used was Classroom Action Research (CAR) following the Kemmis and McTaggart model, which involves two cycles of planning, acting, observing, and reflecting. The subjects were 30 students, and data were gathered through tests, observations, field notes, and documentation. The results demonstrated a significant improvement in students' abilities. In Cycle I, the percentage of students achieving the KKM was 66.6%, as many still struggled with providing mathematical reasons and distinguishing between different concepts. After implementing improvements in Cycle II, such as heterogeneous pairing and mandatory classroom interaction, the success rate increased to 83.3%. This outcome surpassed the 80% success indicator established for the study. Progress was noted across all indicators, including defining concepts and using mathematical representations. In conclusion, the Think Pair Share model effectively enhances mathematical understanding by encouraging independent thought, collaborative discussion, and the active sharing of ideas.